ANALYSIS OF STUNTING INCIDENTS OGAN KOMERING ULU REGENCY IN 2024 - Elentius, Nora; Lilis Suryani; Akhmad Dwi Priyatno (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Stunting represents a significant nutritional issue in Indonesia must be solved to achieve the health success indicators outlined in the Millennium Development Goals (MDGs). This research aims to determine the factors associated with the incidence of stunting in the Tanjung Lengkayap Community Health Center Working Area, Lengkiti District, Ogan Komering Ulu Regency in 2024. Quantitative research design with a cross-sectional approach. The population of this study were all parents of children under five who visited the Tanjung Lengkayap Community Health Center, Lengkiti District, Ogan Komering Ulu Regency in 2024. The sample in this study consisted of 99 respondents. The sampling method uses purposive sampling. This research was carried out from March 22 to April 25 2024. Data was collected using a research questionnaire. Bivariate data analysis using Chi-Square and multivariate tests with logistic regression. The research results showed that there was a relationship between giving MP-ASI (p value 0.04) and body mass index (p value 0.015). There is no relationship between mother's age (p value 0.35), comorbidities (p value 0.61) and smoking habits (p value 0.58) with the incidence of stunting in the Tanjung Community Health Center working area Lengkayap Lengkiti District, Ogan Komering Ulu Regency in 2024. The most dominant factor in the incidence of stunting is body mass index (BMI) (p value 0.032) OR (2.68). The conclusion of this study is the provision of MP-ASI feeding and body mass index significantly influence the incidence of stunting. Community health centers should screen children under five who are at risk of stunting, or have a history of being at risk of stunting